Sufficient conditions for the convergence of the V. A. Marchenko asymptotic series for eigenvalues of the Sturm–Liouville problem - Makarov, V. L. (Reports of the National Academy of Sciences of Ukraine, 2014)
We state sufficient conditions for the convergence of the V. A. Marchenko asymptotic series for where λn are the eigenvalues of the Sturm–Liouville problem with polynomial potential, by using the functional discrete method.